Dapagliflozin acutely improves kidney function in type 2 diabetes mellitus. The PRECARE study. (September 2022) - Lazzaroni, Elisa; Lunati, Maria Elena; Montefusco, Laura; Pastore, Ida; Chebat, Enrica; Cimino, Vincenzo; Morpurgo, Paola Silvia; Muratori, Milena; Plebani, Laura; Bolla, Andrea; Rossi, Antonio; Vallone, Luciana; et al.
Abstract: Dapagliflozin has been demonstrated to improve glycemic control, blood pressure, and body weight in type 2 diabetes mellitus (T2D); indeed, it can also reduce the risk of progression to renal failure, of hospitalization for heart failure and of cardiovascular death. We aim to investigate the acute effect of Dapagliflozin on kidney function in the common clinical practice in T2D. This is a study including 1402 patients with T2D recruited from 11 centers in Lombardia, Italy, who were evaluated at baseline and after 6 months of treatment with Dapagliflozin 10 mg per day. The primary outcome of the study was the change in HbA1c, while the secondary outcomes were modification of weight, BMI, systolic and diastolic pressure, creatinine, eGFR and albuminuria status. After 24 weeks of treatment with Dapagliflozin, a reduction in Hb1Ac was observed (−0.6 ± 1.8%) as well as in BMI (−1.5 ± 5.2 kg/m 2 ). Statistically significant changes were also found for systolic and diastolic blood pressure, cholesterol and triglycerides. Interestingly, a statistically significant acute improvement of kidney function was evident. Our analyses confirm the beneficial effects of dapagliflozin after 6 months of therapy, with improvements of glycemic and lipid profiles, blood pressure, BMI. Finally, an acute positive effect on albuminuria and KIDGO classes was observed during a 6 months treatment with dapagliflozin in patients with T2D. Graphical Abstract: ga1